Toxocara canis Infection Alters lncRNA and mRNA Expression Profiles of Dog Bone Marrow - Zheng, Wen-Bin; Zou, Yang; Liu, Qing; Hu, Min-Hua; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow, is the main hematopoietic organ that produces red blood cells, granulocytes, monocyte/macrophages, megakaryocytes, lymphocytes and myeloid dendritic cells. Many of these cells play roles in the pathogenesis of Toxocara canis infection, and understanding how infection alters the dynamics of transcription regulation in bone marrow is therefore critical for deciphering the global changes in the dog transcriptional signatures during T. canis infection. In this study, long non-coding RNA (lncRNA) and messenger RNA (mRNA) expression profiles in the bone marrow of Beagle dogs infected with T. canis were determined at 12 hours post infection (hpi), 24 hpi, 96 hpi and 36 days post infection (dpi). RNA-sequencing and bioinformatics analysis identified 1,098, 984, 1,120 and 1,305 differentially expressed lncRNAs (DElncRNAs), and 196, 253, 223 and 328 DEmRNAs at 12 h, 24 h, 96 h and 36 d after infection, respectively. We also identified 29, 36, 38 and 68 DEmRNAs potentially cis-regulated by 44, 44, 51 and 80 DElncRNAs at 12 hpi, 24 hpi, 96 hpi, 36 dpi, respectively. To validate the sequencing findings, qRT-PCR was performed on 10 randomly selected transcripts. Many altered genes were involved in the differentiation of bone marrow cells. GO of DElncRNAs, and GO and KEGG pathway analyses of DEmRNAs revealed alterations in several signaling pathways, including pathways involved in energy metabolism, amino acid biosynthesis and metabolism, Wnt signaling pathway, Huntington's disease, HIF-1 signaling pathway, cGMP-PKG signaling pathway, dilated cardiomyopathy and adrenergic signaling in cardiomyocytes. These findings revealed that bone marrow of T. canis-infected dogs exhibit distinct lncRNA and mRNA expression patterns compared to healthy control dogs. Our data provide novel insights into T. canis interaction with the definitive host, and shed light on the significance of non-coding portion of the dog genome in the pathogenesis of toxocariasis.